Scheduling and Network Analysis on Cooling Water Pipe Fabrication Project - Silvianita Silvianita; Daniel Mohammad Rosyid; Ekky Rizky (International Journal of Offshore and Coastal Engineering, 2022)
Optimizing costs and time and manpower planning are very important in project management. The case study raised in this research is a cooling water pipe fabrication project with a processing time duration of 231 days and a project cost allocation of Rp. 306,545,488,000. The method used to control project delays is earned value analysis, and to optimize the project is done by shortening the project duration and minimizing project cost losses using the crash program method. The results of the earned value analysis stated that the project experienced delays, exceeded budget costs and was subject to project delays penalties, which was 340 days of completion time more than 111 days from the planned time and with a total final project cost of Rp.331,813,410,524.46 more than Rp. 25,267,922,524.44 of the costs that have been prepared. Then an effort was made to accelerate the duration of the project with three scenario options. From the results of the crash cost calculation, it is found that the final total cost estimate for scenario 1 with 3 hours overtime is Rp.289,043,553,541. Scenario 2, the estimated total final cost with 4 hours overtime is Rp.289,051,063,021 and scenario 3 the estimated total final cost with the addition of workers is Rp. 289,310.359,861. So, the scenario that can be used by PT. X in order to minimize losses is to impose 3 hours overtime with an estimated total final cost of Rp.289,043,553,541.